Chemoselective Reduction of Tertiary Amides to Amines Catalyzed by Triphenylborane. Issue 42 (6th October 2016) - Mukherjee, Debabrata; Shirase, Satoru; Mashima, Kazushi; Okuda, Jun
Abstract: Triphenylborane (BPh3 ) was found to catalyze the reduction of tertiary amides with hydrosilanes to give amines under mild condition with high chemoselectivity in the presence of ketones, esters, and imines. N, N ‐Dimethylacrylamide was reduced to provide the α‐silyl amide. Preliminary studies indicate that the hydrosilylation catalyzed by BPh3 may be mechanistically different from that catalyzed by the more electrophilic B(C6 F5 )3 . Abstract : The simple borane triphenylborane (BPh3 ) catalyzes the chemoselective reduction of tertiary amides by hydrosilanes to give amines in the presence of halogen, ester, nitro, cyano, ketone, and imine groups. Conjugated amides are reduced to α‐silyl amides.